Inovasi Pelayanan Publik Melalui Aplikasi Jalantol (Jatirenggo Pelayanan Terpadu Online) di Desa Jatirenggo Kecamatan Glagah Kabupaten Lamongan - Rejaningtyas, Eva Septiana; Eprilianto, Deby Febriyan (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The Village Government of Jatirenggo in Glagah district, Lamongan Regency has initiated efforts to enhance public services through the introduction of an innovative application called Jatirenggo Integrated Online Services (JALANTOL). This web- and Android-based platform was developed to facilitate various online community services, including administrative processes, promotion of local UMKM, news and announcements, complaint submissions, and an e-library. Despite these advancements, some residents still struggle to understand or navigate the features within the application. This study aims to analyze public service innovation through the implementation of the JALANTOL application in Jatirenggo Village. Employing a descriptive qualitative method, the research is grounded in the innovation success theory by Bugge et al. (2018), which includes six key indicators: governance and innovation, sources of ideas for innovation, innovation culture, capabilities and tools, objectives, outcomes, drivers and obstacles, and collecting innovation data for single innovation. The findings reveal that the development of JALANTOL aligns with governance standards and has been socialized to the public. The innovation stemmed from the Village Head’s response to technological progress and the needs of a mobile population. The culture of innovation is evident through leadership support and active problem-solving by village officials. Additionally, most staff and residents have the skills to operate the system, supported by training and infrastructure improvements. The goals of the application are largely being met, as many residents have adopted it for public service use, despite persistent technical challenges such as server downtime. Collaboration with various stakeholders continues to improve the application through feature additions and interface updates.